Oris prvih let praznovanja novoletne jelke v Sloveniji - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2016)
The article presents New Year's tree celebrations accompanied by the arrival of Father Frost after the Second World War. Following the Soviet Union's example, the event was introduced by the new communist regime to oust St Nicholas and Christmas celebrations from public spaces. It describes the main development phases of New Year's tree celebrations in the period from late 1947 to 1954/55, when the celebration evolved from a mass children's holiday to a family holiday and its basic components more or less took shape, becoming (to some people) "traditional". The celebrations in Ljubljana are described in detail, as they kind of set an example for other places in Slovenia
Keywords: ljudski prazniki; ljudski običaji; praznovanja; Public holidays in Slovenia; novo leto; Slovenia; Slovenija; 1947/1955; zgodovinski pregledi